2018
DOI: 10.3390/molecules23040818
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Analysis of Gigantol from Dendrobium officinale with Response Surface Methodology

Abstract: In order to optimize the extraction of gigantol from Dendrobium officinale, the influence of methanol concentration, ultrasonic temperature, and liquid ratio on extraction efficiency was analysed by the response surface analysis method. The results show that the extraction rate reached a maximum when the methanol concentration was 92.98%, the solid-liquid ratio was 27.2 mL/g, and the extraction temperature was 41.41 °C. The content of gigantol of Dendrobium officinale in leaves was significantly higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The p-values of the lack-of-fit were 0.9071 and 0.0562, respectively, and each was not significant (p > 0.05) relative to the pure error. This shows that the quadratic model is statistically suitable for predicting responses [50]. The coefficients of variation (CV) were determined as 4.13% and 9.75% for each model.…”
Section: Optimization Of Thermal-alkaline Pretreatment By Rsmmentioning
confidence: 83%
“…The p-values of the lack-of-fit were 0.9071 and 0.0562, respectively, and each was not significant (p > 0.05) relative to the pure error. This shows that the quadratic model is statistically suitable for predicting responses [50]. The coefficients of variation (CV) were determined as 4.13% and 9.75% for each model.…”
Section: Optimization Of Thermal-alkaline Pretreatment By Rsmmentioning
confidence: 83%
“…ANOVA was used to evaluate the optimization results. A small p-value indicates a significant influence on the response variables [ 7 ]. The model had a correlation p value of 0.0003 < 0.01, which indicated that the optimization model was significant.…”
Section: Resultsmentioning
confidence: 99%
“…A confirmatory experiment was performed based on the optimal extraction conditions obtained from the aforementioned experiments. A method was considered credible if the percentage error was less than 10% [ 7 ]. The average experimental value for the flavonoid extraction efficiency model was 35.45 ± 0.34 mg/50 mL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gigantol is a bibenzyl compound extracted from the Thai orchid, Dendrobium draconis ( 5 ). In China, gigantol is an active ingredient commonly extracted from Dendrobium officinale , which is a valuable Chinese herbal medicine ( 6 , 7 ). Plants of the Dendrobium genus have been reported to display immunomodulatory, neuroprotective, antioxidant and antitumor effects ( 8 ).…”
Section: Introductionmentioning
confidence: 99%